Fertilizing and Liming Forage Crops - Yoana C. Newman; Cheryl Mackowiak; Rao Mylavarapu; Maria Silveira (EDIS)
Revised! SS-AGR-176, an 8-page fact sheet by Y. C. Newman, C. Mackowiak, R. Mylavarapu, and M. Silveira, provides a basic overview of nutrient management for forage crops and fertilization recommendations for specific forages. Published by the UF Department of Agronomy, January 2008.